Creating an Instrument Maintenance Shop + Arranging Music From Diverse Sources - Johnson, Leo C.; Ostrander, Phillip (My University, 2019)
The purpose of this project is twofold. The first component was to create an economically and environmentally sustainable instrument maintenance and cleaning shop in Haas Fine Arts Center. The second component involved developing music arrangement skills in order to expand the trombone ensemble repertoire in a more diverse direction.
Color poster with text and photographs.
Keywords: Instruments maintenance and repair; Multiculturalism; Music education; Posters